Stability of iodine in iodized salt during salt iodization - Montecastro, Alan Collado
The main objective of this study was to determine the stability of iodine in iodized salt during salt iodination. This is in response to the ASIN Law (An Act on Salt Iodization Nationwide) which requires all importers, traders, and manufacturers of salt to solely trade and produce iodized salt for human consumption (National Nutrition Council, 1996). This study was conducted to assist the local iodized salt producers in manufacturing iodized salt that would meet the requirements set by the Philippine Government. This study was also aimed at establishing a system of testing the iodine in iodized salt. The first phase of the study dealt with the observation and evaluation of the individual processes of the 2 commercial companies who participated in this study. The 2 local iodized salt producers who participated in this study were Manufacturer A and Manufacturer B. Processes were established by observing the entire process flow of the individual companies. The second and third phase of this study focused on the production and quality assessment of the raw and iodized salt of both companies. The second phase dealt with the physic-chemical analyses of the salt samples from both companies. The study showed that Manufacturer A had an content of 74% for its raw salt. The results from Manufacturer B showed that the raw salt used contained 7.9% moisture, 0.83% filth and a 92% NaCl content. The iodized salt of Manufacturer A was characterized with an 8.5% moisture, 0.53% filth and a 70% NaCl content, while Manufacturer B had an 8.1% moisture, 0.79% filth and a 90% NaCl content. The t-test for paired difference at a 0.05 level of significance showed that there was a significant difference between the moisture content of the raw salt and NaCl% of raw and iodized salt of Manufacturer A and Manufacturer B. There was however, no significant difference between the moisture content of iodized salt and filth content of the raw and iodized salt of the 2 manufacturers. The third phase dealt with the analysis of iodine content of the salt during the following stages: before iodization; right after iodization; and after a day of storage under ambient conditions. The iodine content of salt samples from both companies were below the sensitivity of the method which was 1.1 ppm. . Right after iodization, the salt of Manufacturer A had 47.06 ppm while Manufacturer B had 24.67 ppm. After 1 day of storage Manufacturer A had 46.55 ppm and salt of Manufacturer B had 24.67 ppm. The finished products were then subjected to the Military Standard of analysis and 13 samples per manufacturer were assessed for iodine content based on 2 standards: the standard set-up by the World Health Organization at 34-66 ppm of iodine (WHO, 1996) and the one set-up by the Philippine Government at 60-100 ppm (National Nutrition Council, 1996) of iodine. The Military Standard was done after 1-2 weeks of storage under ambient conditions. Based on the WHO standard, the batch of iodized salt of Manufacturer A was rejected because 3 samples among 13 were below specifications. The batch of iodized salt produced by Manufacturer B was also rejected because all samples did not meet the specifications. Based however on the standards of the Philippine Government, all samples from both companies did not meet the requirements and both batches were rejected.